“An Author’s Relationship with His Audience”: the earliest autobiographical work of local Malay - Hamdan, Rahimah; Sujud, Arbaie (Medwell Journals, 2016)
This study describes the confusion regarding the term ‘autobiography’ which is being disputed by some scholars of Malay literature as well as proves that Tarikh Dato’ Bentara Luar Johor, written by Mohamad Salleh Perang is the earliest Malay autobiography. In the early 20th century, the colonial scholars were of one mind in their recognition of Kisah Pelayaran Abdullah and Hikayat Abdullah, written by Abdullah Munshi as the first Malay autobiographical works. This recognition, in turn, led to the division of the history of Malay literature into the traditional and modern periods. Nevertheless, the recognition accorded to Abdullah Munshi gave rise to a controversy when it was said that his works were not composed for the ruler and the Malay audience but for the Western colonialists. The autobiographical works that deserve recognition should be those that were written for the ruler and the Malay audience because of the close relationship between the Malay community and their ruler. By using C.W. Watson’s scale for Western autobiographies, this study discusses the pertinence of Tarikh Dato’ Bentara Luar Johor as the earliest autobiographical work of a local Malay. Indirectly, the recognition of Abdullah Munshi’s work as the first autobiography should be reviewed because it would not be fair to recognize a work whose contents were hurtful to the ruler and the Malay audience. In conclusion, this study has triggered a re-interpretation of the history of Malay literature in this country if the autobiography genre is used to mark the beginning of the ‘modern’ period.